Rene policistico autosomico dominante: dalla patogenesi alla terapia - Giovanni Piscopo (AboutScience Srl, 2022)
Autosomal Dominant Polycystic Kidney (ADPKD) is the most common genetically determined kidney disease of Mendelian inheritance. It has a variable prevalence, depending on the case series, from 1:1,000 to 1:2,500, and represents the fourth cause of renal failure in the world. It is part of the so-called ciliopathies and is mainly caused by the mutation of two genes: PKD1, located on chromosome 16p and the PKD2 gene, located on chromosome 4q and coding for Polycystin-2 (PC2); although two other disease-causing genes have recently been identified: DNAJB11 and GANAB. These two proteins consist, respectively, of a calcium channel and a transmembrane receptor, and they play a decisive role in regulating cell proliferation, division and differentiation, apoptosis and autophagy. The molecular mechanisms underlying the genesis of the cysts are multiple and for this reason not yet completely understood and although several of them have been the subject of preclinical and clinical studies aimed at evaluating the efficacy of therapies that could continue to interfere in a specific way, to date, only tolvaptan and octreotide-LAR (the latter only in Italy) have been approved for the treatment of renal disease secondaryto ADPKD. Here, we therefore recapitulate the different pathogenetic pathways in ADPKD and the possible therapeutic treatments.